PENGARUH MODEL PEMBELAJARAN INQUIRY TRAININGTERHADAP HASIL BELAJAR SISWA PADA MATERI POKOK SUHU DAN KALOR DI KELAS X SEMESTER II SMA AL-FATTAH MEDAN - Nasution, Hermansyah; Derlina, Derlina (JURNAL IKATAN ALUMNI FISIKA, 2016)
This study aims to determine the effect of Inquiry learning model training on learning outcomes of students in the subject matter of Temperature and Heat in class X Semester II SMA AL-Fattah Medan and see the activities of students using model Inquiry Training. This research is a quasi-experimental. The population in the study were all students of class X SMA AL-Fattah Medan. Sampling was done by cluster random sampling by taking two classes of fourth grade, where class X-1 by the number of students 41 people as an experimental class taught by learning model Inquiry Training while class X-2 by the number of students 43 people as the control class was taught by Conventional learning. The instrument used in this study are: to test the learning outcomes in the form of an essay test, amounting to 8 questions that have previously been tested its validity by experts, and the instrument used to determine students learning activity is observation sheet. The results of this study gained an average pretest score for the experimental class and control class 33.72 36.66. Testing for normality in the experimental class of data obtained Lhitung = 0.0968 and Ltabel = 0.1384, for classroom control with Lhitung = 0.1209 and Ltabel = 0.1351, thus obtained Lhitung <Ltabel. Results of homogeneity test calculations obtained F count = 1.15 and = 1.68 Ftabel so Fhitung <F table, then both samples come from homogeneous group. The treatment given to the two different classes, the experimental class learning model Inquiry Training and grade control with conventional learning models, after learning given postes finished with an average yield of 56.48 experimental class with a standard deviation of 9.99 and grade control 52.54 with a standard deviation of 8.87. The average value of the entire student activity experimental class 78.05 while the control class is 50.72. The result of a linear equation with the equation y = + 29.728 0,7297x obtained that no influence using model Inquiry Training on learning outcomes of students in the subject matter and the heating temperature in class X SMA AL-Fattah Medan by 56.02%.